Pra-Boat Sdn.Bhd (Furniture) / Ahmad Hariz Mohd Hishamuddin ... [et al.] - Ahmad Hariz, Mohd Hishamuddin; Amirul Azwan, Abdul Aziz; Natasha Aziera, Shaifol Bahari; Syahirah, Mat Sahizol Raduan (2019)
Pra-Boat Sdn Bhd provides sophisticated and maintaining services of furniture, that'll minimize our customer's space usage and maximize their comfort. Our team will ensure that the furniture is long-lasting. Pra-Boat Sdn Bhd is headquartered in the Bandar Seri lskandar and incorporated in Sota, Perak. The company is owned by Azwan Aziz and 3 other partners. Azwan has extensive experience in manufacturing furniture while the others are very experienced in managing activities. Our clients are the one who seeks more space in their home while having comfort and being able to move their furniture anywhere easily. Pra-boat Sdn Bhd provides a variety of sophisticated furniture and its services, which include: • Portable & space-saving furniture • Multi-functioning furniture • Furniture customization • Fix and repair old furniture Across Malaysia, the furniture business has seen an explosion of growth over the last three years. Seri lskandar is an affluent area with a high furniture demand. Our market research has shown that 9 out of 10 people polled in Seri lskandar would need to save space in their home while doing various task and 6 out of 10 would want bring their furniture anywhere. • While there are currently 4 businesses selling furniture in Seri lskandar, none of them are providing space-sawy furniture and any related services. • Pra-Boat's marketing strategy is to emphasize the quality of our furniture, we provide multifunctioning design and the availability of our services. Small-sized homeowners, for instance, will be able to do anything he want despite having a limited space. • All furniture services will be provided by certified staff. • All employees are insured and bonded. Based on the size of our market and our defined market area, our sales projections for the first year are RM9, 177,600. We project a growth rate of 5% per year for the first three years. We have plan to aggressively build our client base through newspaper, flyers, signboard, banners, website, social media, and direct mail advertising. The organized services and sophisticated furniture that Pra-Boat Sdn Bhd will provide is sure to appeal to every busy homeowners throughout the Seri lskandar area.